تأثير وسيلة بطاقة الصورة في حفظ المفردات العربية لطلاب الصف الثامن في المدرسة المتوسطة الإسلامية الحكومية ٩ بيسسير سلاتان - مايسا, ننجسيه ترى; حسنى, أرمان (International Journal of Education, Management, and Technology, 2024)
The problem of this research is the students' interest in memorizing Arabic vocabulary decreased because the Arabic language teacher did not use the picture card teaching aids, but the Arabic language teacher used the blackboard method. Which causes a lack of students' understanding in memorizing Arabic vocabulary, which causes a decrease in students' scores in learning the Arabic language. The objectives of this research are to find out the effect of the picture card method in memorizing Arabic vocabulary in the eighth grade of the state Islamic middle school 9 Becisir Salatan. In this research, the researcher used an empirical researchtrue experimental kind ofpretest-postest control group design. The research population is the eighth grade students, and they number 54 people, and the research sample is the eighth grade students (1) in the experimental class, and they number 24 people, and the eighth grade (2) the control class, and they number 30 people. Sample selection method random sampling. The research tools used in this research are testing and documentation. for data analysisThe researcher usedT-test. The results of the search is The value of the pre-test and the value of the post-test were indicated with significance (sig-2 tailed) p = 0.000 <0.05. So there is Positive effect of the picture card method in memorizing Arabic vocabulary in the eighth grade of the state Islamic intermediate school 9 Becisir Salatan.